Respuesta :

Answer:

a. x × (y + z) = -13/240

c. x × (y × z) = 1/24

Step-by-step explanation:

The given values of the variables are;

[tex]x = \dfrac{-1}{8} , y = \dfrac{-2}{5} \ and \ z = \dfrac{10}{12}[/tex]

a. x × (y + z) = (x × y) + (x × z), by distributive property

Plugging in the values gives;

[tex]\dfrac{-1}{8} \times \left (\dfrac{-2}{5} + \dfrac{10}{12} \right) = \left ( \dfrac{-1}{8} \times\dfrac{-2}{5} \right) + \left ( \dfrac{-1}{8} \times \dfrac{10}{12} \right)[/tex]

[tex]\dfrac{-1}{8} \times \left (\dfrac{-2}{5} + \dfrac{10}{12} \right) = \dfrac{-1}{8} \times \left (\dfrac{13}{30} \right) = \dfrac{-13}{240}[/tex]

[tex]\left ( \dfrac{-1}{8} \times\dfrac{-2}{5} \right) + \left ( \dfrac{-1}{8} \times \dfrac{10}{12} \right) = \dfrac{1}{20} + \dfrac{-5}{48} = \dfrac{-13}{240}[/tex]

Therefore;

[tex]\dfrac{-1}{8} \times \left (\dfrac{-2}{5} + \dfrac{10}{12} \right) = \left ( \dfrac{-1}{8} \times\dfrac{-2}{5} \right) + \left ( \dfrac{-1}{8} \times \dfrac{10}{12} \right) = \dfrac{-13}{240}[/tex]

c. x × (y × z) = (x × y) × z

Plugging in the values for 'x', 'y', and 'z' gives;

[tex]\dfrac{-1}{8} \times \left (\dfrac{-2}{5} \times \dfrac{10}{12} \right) = \left ( \dfrac{-1}{8} \times\dfrac{-2}{5} \right) \times \left ( \dfrac{10}{12} \right) = \dfrac{1}{24}[/tex]